Elaboração e caracterização de farinha de trigo e pão francês enriquecidos com colágeno hidrolisado - Graça, Laís Borges (2020)
Functional foods are those that have compounds or nutrients with the ability to promote health and decrease the risk of disease when consumed (ROBERFROID, 2000). Collagen is one of those ingredients that has been added to foods in order to promote therapeutic and functional properties. Collagen in bread making is one of several possibilities of use that this protein can have, but there are few studies of the effects of its presence in bread making and even less in the formulation of French bread produced with wheat flour. In this context, the objective was to study the feasibility of using hydrolyzed collagen in French bread as a collagen consumption option since French bread is the most important type of bread within Brazilian bakeries, as its consumption corresponds to 53% of the total of bread in the country (ABIP, 2011). The proportions used were 0.75%, 1.5% and 3% and the flour and breads produced from them were physically and chemically categorized. According to the physicochemical results of the flours, the addition of collagen changed the results of Falling number, gluten index, granulometry, increased the fatty acidity and protein content in relation to the standard. It was possible to observe in the breads that the addition of hydrolyzed collagen changed the color of the breads making the skin and crumbs darker. As for texture, only significant differences were observed in the formulation with 3% collagen and for the adherence and chewability attributes, with no significant change for the parameters hardness, cohesion and elasticity. And in the FTIR spectra, a similarity in structure can be observed in all concentrations in relation to the standard sample, however it provided excellent data to explore the effect of the addition of collagen in the formulations.